2017
DOI: 10.1007/s00213-017-4546-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of synthetic cannabinoids on executive function

Abstract: This study showed impairment of executive function in synthetic cannabinoid users compared with recreational users of cannabis and non-users. This may have major implications for our understanding of the long-term consequences of synthetic cannabinoid based drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 69 publications
7
68
1
6
Order By: Relevance
“…2 A three-week SC use has been reported to have speech-pausing and avoidant eye contact effects. However, the cognitive functions are reported to be severely impaired in chronic use for eight weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 A three-week SC use has been reported to have speech-pausing and avoidant eye contact effects. However, the cognitive functions are reported to be severely impaired in chronic use for eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“…cination, panic attack, anxiety and depression. 2,28 It has also been reported that that there is an increase in the number of suicides following the use of SCs. 28 In our study, supporting the literature, the depression scores of patients with SCs use disorder were significantly higher than healthy control group.…”
Section: : Independent-samples T-testmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] These modifications are not restricted to 3-naphthoylindoles, and several regioisomers and homologues of methoxybenzoylindole SC RCS-4 (5) have also been reported 29,30 despite no precedent in the scientific literature, with position of methoxy substituent affecting cannabinoid potency in vitro. 34,35 Although this compound was unprecedented in the scientific literature at the time of its discovery, other benzylic indole-3-carboxamides had been reported as potent, water-soluble CB 1 receptor agonists. 34,35 Although this compound was unprecedented in the scientific literature at the time of its discovery, other benzylic indole-3-carboxamides had been reported as potent, water-soluble CB 1 receptor agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Acute SC poisoning can lead to hospitalization. Recent studies have shown a decline in the executive function in SCs' users compared with recreational users of cannabis and non-users [28]; they also present more symptoms of confusion, disorientation and incoherent speech than consumers of natural cannabis [29].…”
Section: Adverse Effectsmentioning
confidence: 99%